Embedding SDGs in Ethiopian Higher Education: Overcoming Challenges, Seizing Opportunities, and Forging Inclusive Pathways for Digital-Era Transformative Learning - Goshu, Belay Sitotaw; Woldeamanueal, Melaku Masresha (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2013)
This study explores the integration of sustainability and global citizenship in Ethiopian higher education institutions (HEIs) through human-centered strategies and actionable recommendations. Across 12 institutions, including Hawasa and Jigjiga, six strategies, such as "Integrate SDG Modules" and "Adopt Green Campus Policies," yielded a mean priority score of 7.98 (SD = 0.87) and a feasibility score of 7.15 (SD = 0.94), reflecting enthusiastic yet constrained potential. Statistical analysis, including ANOVA (p = 0.018) and regression (R² = 0.46), highlights policymakers’ leadership in green policies (8.8, 8.2) and institutions’ success with sustainability clubs (8.5, 7.9), while digital tools lag (7.0, 6.0) due to infrastructure gaps. The findings reveal a resilient spirit, with strong correlations (e.g., r = 0.82) suggesting synergy in community-driven efforts, yet cultural and rural barriers persist. Conclusions emphasize tailored support to empower educators, students, and communities, fostering a sustainable, globally aware future.